La coopération entre élèves en EP : entre effets avérés et difficultés de mise en œuvre - Sandra Jourdan; Jacques Méard; Roberta Antonini Philippe (Éducation et Socialisation)
The rapid rise of information media is responsible for an evolution shift that does not seem to be mirrored in the modalities of school education. In this "unchanging class in a changing world", interactions between students are frequently thought of as parasitic. However, cooperative models seem to give promising results on motivation and learning according scientific literature. Even in PE, it seems that teachers don’t use them frequently deliberately to design group work during lessons. Using the theoretical and methodological framework of the Clinic of activity (Cultural Historical Activity Theory- CHAT), more precisely the Leontiev's model (1984) that allows to identify motives and operations in the activity of workers (here, PE teachers) and the leveraging of the first results, it would be interesting to verify the reality of an insufficient use of cooperative work in the Swiss context and, if so, to better understand what in the teacher’s activity could explain it.